The Semantics of Verbs in Mam Jalal's Presidential Speeches - Bakhtiar Awla Rashid; Amir Rafiq Awlla (Zanco Journal of Humanity Sciences)
Arabic stands out for its inflectional system and is described as a derivational and inflectional language. It plays a crucial role in constructing and understanding discourse.